DHF Learning Module Design for Elementary School Teachers Within the Region Kuta Raja District, Banda Aceh City - Hermansyah; Ismail; Munazar; Halimatussakdiah (Postgraduate, University of Mataram, 2023)
The high number of Dengue Hemorrhagic Fever (DHF) cases from year to year and the endemic status of DHF in Kutaraja District, Banda Aceh City encourages us to always make efforts to reduce the morbidity rate of DHF. The involvement of elementary school teachers is very important to participate in DHF control which will teach their students. This study was conducted to assess the effect of before and after administration of the DHF learning module on the average knowledge score of 90 grade IV and V elementary school students in the Kutaraja District, Banda Aceh City. The quasi-experimental method and Focus Group Discussions involving schools and Puskesmas when designing DHF learning modules were conducted. One-group pretest-posttest design, consisting of 25 questions that were analyzed using the Wilcoxon Signed Ranks Test. The study results obtained an average pre-test score of 76.6% and a post-test average value of 90.6%. The DHF learning module was able to increase elementary school students' knowledge. The provision of DHF material by elementary school teachers through modules can be done to students to increase students' knowledge so that they can participate in reducing the incidence of dengue hemorrhagic fever. Â